2017
DOI: 10.1155/2017/6746989
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Hepatotoxicity of Fluconazole, Ketoconazole, Itraconazole, Terbinafine, and Griseofulvin in Rats

Abstract: Oral ketoconazole was recently the subject of regulatory safety warnings because of its association with increased risk of inducing hepatic injury. However, the relative hepatotoxicity of antifungal agents has not been clearly established. The aim of this study was to compare the hepatotoxicity induced by five commonly prescribed oral antifungal agents. Rats were treated with therapeutic oral doses of griseofulvin, fluconazole, itraconazole, ketoconazole, and terbinafine. After 14 days, only ketoconazole had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
6
23
0
1
Order By: Relevance
“…Azole antifungal agents, including ICZ, are known to have hepatotoxicity as a side effect and possibly to induce cholestasis and jaundice [29][30][31][32]. As increases in liver enzymes are observed in cats with FIP, the development of adverse effects after ICZ administration was of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Azole antifungal agents, including ICZ, are known to have hepatotoxicity as a side effect and possibly to induce cholestasis and jaundice [29][30][31][32]. As increases in liver enzymes are observed in cats with FIP, the development of adverse effects after ICZ administration was of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Terbinafine is an attractive medication because of its once‐daily dosing and has minimal drug–drug interactions (Ibrahimi, Gunawardane, Sepehr, & Reynolds, ). Although terbinafine has been reported to induce hepatic injury, it is associated with a lower risk of clinically significant transaminitis than other antifungal agents (Khoza, Moyo, & Ncube, ). Cutaneous adverse effects occur in 1–3% of patients on terbinafine, and the incidence of serious side effects, including AGEP, subacute cutaneous lupus erythematosus, and erythema multiforme, is only 0.04% (Eyler et al, ).…”
Section: Case Discussionmentioning
confidence: 99%
“…Therefore, beside antifungal potential, it is one of the few available remedies for Cushing's syndrome . Although this drug is effective in decreasing cortisol and reducing the clinical effects of Cushing's syndrome, it is life‐threatening due to the risk of severe hepatotoxicity …”
Section: Introductionmentioning
confidence: 99%
“…7 Although this drug is effective in decreasing cortisol and reducing the clinical effects of Cushing's syndrome, it is life-threatening due to the risk of severe hepatotoxicity. 8 Moreover, it has been reported that this antifungal agent is able to induce a variety of heart function side effects, such as long-QT syndrome 9 and ventricular arrhythmias. 10 Although, clear mechanism of this action is not obvious, it is in center of sanctifies attention.…”
mentioning
confidence: 99%